A MONITORIA ACADÊMICA COMO CANAL DIALÓGICO NO PROCESSO DE FORMAÇÃO DO NUTRICIONISTA - Ana Eliza Port Lourenço; Laís Vargas Botelho; Márcia Regina Viana; Amábela de Avelar Cordeiro; Maria Gouvêa de Lacerda; Inglidy Oliveira de Souza (Universidade do Estado do Rio de Janeiro, 2017)
Purpose: To report the monitoring experience in the Axis of Collective Health of the Nutrition Course of the Federal University of Rio de Janeiro, Campus UFRJ-Macaé, Brazil, reflecting on this practice as a training strategy for nutritionists.  Methodology: The monitoring in the Axis is delineated according to the conception of non-hierarchical education and reciprocity, worked respectively by Paulo Freire and Simone de Beauvoir. Content analysis of the experience reports of the authors in the scope of the monitoring was carried out, in a self-assessment perspective. Results and Discussion: This experience revealed the potential of monitoring as a pedagogical strategy in the training of nutritionists, by adding humanization and providing a dialogical channel of horizontal and reciprocal learning. Monitoring contributes to professor training, above all by encouraging professors to rethink their pedagogical practice to better guide the monitors. It also stimulates the protagonism of the students during their learning, being able to favor greater professional autonomy. Time mismatch to work as a team and little student adherence to the activities proposed by the monitors were the main obstacles identified. Within the scope of the courses, possible ways to overcome such difficulties have been tested, but with little success. Conclusions: It is imperative to discuss monitoring in higher academic spheres, aiming to adjust the curriculum of the courses, in order to incorporate a specific time for this purpose. This experience advocates the construction of a new institutional culture, in which monitoring is inserted in the academic routine, inherent to teaching, articulated to research and extension, favoring the formation of autonomous professionals, freed and imbued with humanization in health care. DOI: 10.12957/demetra.2017.28675